The strength of Malayness through colonial mimicry in Affifudin Omar’s Tun Tuah - Nurhanis Sahiddan,; Hashim Ismail,; Tengku Intan Marlina Tengku Mohd Ali, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The research on Homi Bhabha’s theory of mimicry in postcolonial literature is no longer new. However, in Malay literature, the application of mimicry in order to analyse such fiction is still rare. This paper seeks to utilise the conceptual framework of Homi K. Bhabha’s colonial mimicry in order to explain the portrayal of the Malay characters in Tun Tuah and eventually analyse the characters’ strength in terms of their Malayness in critical situations or crises. The conceptual framework have been explicated into three major parts for the analysis of the novels in terms of; a) contesting colonisation, b) metonymy of presence, and c) resisting colonialist discourse. Excerpts from the novels will be extracted and presented for analysis under each part of the conceptual framework as mentioned above. A close reading of Tun Tuah will be applied as methodology to explore how the strong Malay characters could be divided into either those who mimic the people of the West, those who truly fit the Malay identity as being conservative Malays or those having both Western values while also holding onto the Malay identity. This study then explains the findings from the analysis on how the Malay characters thrive towards success in the novel Tun Tuah, in the three processes of colonial mimicry. It is found that the final process of colonial mimicry, resisting colonialist discourse displays how the Malay characters in Tun Tuah, particularly Tun Tuah himself, Tun Perak and Sultan Alauddin Riayat Shah’s strategies for economical and life success consists of them challenging the colonialists’ way of life, while focusing on the Malay traditions and Islamic beliefs.